Visual-processing deficits in children with neurofibromatosis type 1: A clinical marker of reading difficulties. (May 2022) - Vernet, Marie; Jover, Marianne; Bellocchi, Stéphanie; Maziero, Stéphanie; Jucla, Mélanie; Tallet, Jessica; Danna, Jérémy; Chaix, Yves; Ducrot, Stéphanie
Abstract: Today's estimates indicate that nearly 50% of children with Neurofibromatosis type 1 (NF1) suffer from reading disabilities, with a high impact on their academic achievement. In addition to the well-documented importance of phonological skills in reading acquisition and neurodevelopmental disorders, visual-attention processes also appear as important factors in learning to read. The present study aimed at assessing the role of visual-processing dysfunction in the high prevalence of reading disabilities in NF1 children and providing a useful tool for clinician in the early detection of reading impairment in this neurogenetic disorder. Forty-two children with NF1 and 42 typically developing children (TD) participated in the study. All were right-handed and did not present intellectual disability or attention deficit hyperactivity disorder. Visual-attention processes were assessed with the Developmental Eye Movement (DEM) test, together with the NF1 children's reading level. NF1 children with and without reading disabilities were then compared. The results showed that visual-processing deficits were highly present among the NF1 children included in our study. Furthermore, poor readers with NF1 presented an increased risk of visual-processing deficits compared to peers. This finding supports the role of visual-processing deficits in the reading difficulties encountered in nearly half of children with NF1. Finally, in NF1 children without intellectual or attention disability, visual-processing deficits emerge as one of the clinical markers of reading disabilities. The study holds important clinical implications both for the identification, by providing a useful screening tool, and the management of reading disabilities in NF1 children. Highlights: Visual-processing deficits are highly present among NF1 children without ADHD. Poor readers appeared to be at increased risk for visual deficits. Visual-processing deficits emerge as a clinical marker of reading impairment in our NF1 sample. Visual processes assessment should become systematic to improve schooling in NF1. The DEM-test is a useful tool in the clinical management of the NF1 without ADHD.